ANALISIS PENGUCAPAN HURUF HIJAIAH TENGGOROKAN PADA ANAK DENGAN GENDANG TELINGA BERLUBANG - Salma Dzuriyati Samiyah; Feby Moch Febrian; Tatang Tatang (Yayasan Haiah Nusratul Islam, 2025)
This study examines the articulation abilities of an 11-year-old girl with a perforated eardrum in pronouncing Arabic throat letters (halqiyah). The study focuses on her articulation of six throat letters خ, غ, ع, ح, ءand ه affected by hearing impairment. Findings show that the perforated eardrum affects the child’s ability to produce dorsovelar and pharyngeal consonants accurately, often resulting in sounds that resemble other similar throat letters. Environmental and psychological support has been beneficial for her language development, encouraging improvements in her articulation skills despite physical limitations. However, auditory challenges continue to affect her pronunciation, highlighting the need for specific educational strategies to aid her learning process.